Applying Buddhist Dharma Principles to Develop the Quality of Public Service Lamphun Muncipality, Lamphun Province - Karki, Litish (MCU Haripunchai Review, 2025)
The purpose of this research is to 1. study the level of service quality provided by Lamphun Municipality, Lamphun Province. 2. Compare the opinions of the community members in Lamphun Municipality regarding the service quality of Lamphun Municipality, Lamphun Province, categorized by personal factors. 3. Propose the application of Buddhist principles to improve the service quality of Lamphun Municipality, Lamphun Province. The research employs a mixed-methods approach, with quantitative research conducted through the distribution of questionnaires to 387 residents of Lamphun Municipality, achieving a reliability value of 0.949, and data analysis using t-tests and F-tests. Qualitative research was conducted through in-depth interviews with 9 key informants and content analysis. The research results revealed that: 1) The overall level of development of the service quality of Lamphun Municipality, Lamphun Province, is at a high level. 2) The results of comparing the opinions of the public in the Lamphun Municipality community regarding the quality of services provided by the Lamphun Municipality, Lamphun Province. 3) The development of service quality should emphasize both ethics and the ability to provide services effectively. This includes fostering good relationships with the public through giving and sacrifice, alongside improving the tangible quality of services. Building credibility by maintaining standards and meeting the needs of the public is essential, as well as incorporating technology to modernize services and align them with the long-term needs of the public.